2017
DOI: 10.18632/oncotarget.14942
|View full text |Cite
|
Sign up to set email alerts
|

Sulfatinib, a novel kinase inhibitor, in patients with advanced solid tumors: results from a phase I study

Abstract: Sulfatinib is a small molecule kinase inhibitor that targets tumor angiogenesis and immune modulation. This phase I study (NCT02133157) investigated the safety, pharmacokinetic characteristics, and preliminary anti-tumor activity of sulfatinib in patients with advanced solid tumors. The study included a dose-escalation phase (50-350 mg/day, 28-day cycle) with a Fibonacci (3+3) design, and a tumor-specific expansion phase investigating the tumor response to treatment. Two sulfatinib formulations were assessed: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…Sulfatinib is a multi-target TKI targeting VEGFR-1/2/3, FGFR1, and colony stimulating factor 1 receptor (CSF1R). A phase I study (NCT02133157) observed an acceptable safety profile and encouraging antitumor activity in patients with advanced solid tumors, particularly in NETs [ 95 ]. At present, one phase II study (NCT02267967) and two phase III studies (NCT02589821, NCT02588170) conducted on advanced NETs are ongoing [ 96 ].…”
Section: Novel Anti-angiogenic Tkis Under Investigationmentioning
confidence: 99%
“…Sulfatinib is a multi-target TKI targeting VEGFR-1/2/3, FGFR1, and colony stimulating factor 1 receptor (CSF1R). A phase I study (NCT02133157) observed an acceptable safety profile and encouraging antitumor activity in patients with advanced solid tumors, particularly in NETs [ 95 ]. At present, one phase II study (NCT02267967) and two phase III studies (NCT02589821, NCT02588170) conducted on advanced NETs are ongoing [ 96 ].…”
Section: Novel Anti-angiogenic Tkis Under Investigationmentioning
confidence: 99%
“…Sulfatinib (HMPL012) is a potent small molecule TKI of VEGFR 1, 2, and 3, FGFR 1, and Colony Stimulating Factor 1 Receptor- CSF1R. Xu et al [ 83 ] investigated the sulfatinib safety, pharmacokinetics, and preliminary antitumor activity in advanced solid tumors. As for other anti-angiogenic drug the most frequent side effects during therapy were proteinuria, hypertension and diarrhea.…”
Section: Vegfr and Hypertensionmentioning
confidence: 99%
“…Surufatinib is a potent TKI targeting VEGF receptors (VEGFR) 1, 2, and 3, FGFR1, and CSF-1R. In preliminary phase I and Ib/II studies surufatinib showed encouraging anti-tumor activity in advanced NENs ( 81 , 82 ).…”
Section: Fgfrs As Therapeutic Target In Nensmentioning
confidence: 99%